Harry Potter and the sorcerer's stone. 1-1 - Rowling, J. K; Grandpre, Mary, (Illustrator) (California : SENSEE, 2021)
Rescued from the outrageous neglect of his aunt and uncle,a young boy with a great destiny proves his worth while attending Hogwarts School for Wizards and Witches.
Chapter Four : The Keeper of The Keys
Braille Books.
This book was made for those with visual impairment.
Keywords: Potter, Harry -- (Fictitious character) -- Juvenile fiction; Granger, Hermione (Fictitious character) -- Juvenile fiction; Weasley, Ron (Fictitious character) -- Juvenile fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Juvenile fiction; Wizards -- Juvenile fiction; Magic -- Juvenile fiction; Schools -- Juvenile fiction; England -- Juvenile fiction; Fantasy fiction